Thermodynamic Behaviour of Hypersensitive Transitions Observed in Some Pr(III) and Nd(III) Systems - Shakuntla Maurya, M.S.; Daya Balani, M.S.; Joshi, G.K. (Asian Journal of Chemistry, 2010)
The saturated anionic ligand environment produced by various organic acids in DMF and DMSO around Pr(III) and Nd(III) ions has been studied with respect to the hypersensitive transition involved in the system. The spectroscopic data for the hypersensitive transition have been correlated with the thermodynamic parameters which yield the thermodynamic behaviour of the said transition. Thermodynamic parameters include thermodynamic efficiency and partition function of the said transition.